INHIBITION ACTIVITY of ESSENTIAL OIL of LEMONGRASS LEAVES (Cymbopogon citratus) ON THE GROWTH OF Escherichia coli, Staphylococcus aureus, AND Vibrio cholerae. - Kirani Paramita, Dwi Ayu; Semadi Antara, Nyoman; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 1 (2014): Maret)
The research aim was to determine the inhibition activity of essential oil of lemongrass (Cymbopogon citratus) on the growth of pathogenic bacteria. This research used a Completely Randomized Design with 5 treatments lemongrass oil concentration in 1% tween 80 namely 1%, 2%, 3%, 4%, 5% (v/v), and each concentration was tested to the three bacteria (Escherichia coli, Staphylococcus aureus, and Vibrio cholerae). Each treatment was repeated 3 times and the data were analyzed by analysis of variance, and followed by Duncan's Multiple Range Test. The results showed that lemongrass oil in tween 80 affected significantly the growth of Escherichia coli, Staphylococcus aureus and Vibrio cholerae. Inhibition against Escherichia coli, Staphylococcus aureus, and Vibrio cholerae at a concentration of 1% produces the highest activity with the inhibition diameter of 6,03 mm, 4,97 mm, and 9,67 mm, respectively. Vibrio cholerae was more sensitive againts lemongrass oil than Escherichia coli and Staphylococcus aureus.
Keywords: 14,